(untitled) (Philological Studies, 2019)
This article is devoted to late Valentin Rasputin’s short story «During Bad Weather» (2003). Mithopoetical subtext of story is investigated in connection with writer’s physiophilosophical concept which was created in 1970–1980’s. The images of the nature are based on Christian symbols; eschatological motives which are used for a negative assessment of a modern civilization, are genetically connected with the bible description of the Apocalypse. At the same time some non-Christian motives join in structure of mifopoetical subtext. Some of mithopoetical images and motives which have close compliances in authentic folklore, allows to raise a question of a deep, or intuitive folklorizm of V. Rasputin’s literary artworks. This type of a folklorizm is based not on direct knowledge of folklore plots and reproduction of them in the art text, but on deep understanding of laws of traditional consciousness. This knowledge allows the writer “to guess” skillfully various folklore models which was unknown to him.